Longitudinal reference ranges for fetal ultrasound biometry in twin pregnancies - Liao, Adolfo Wenjaw (2012)
OBJECTIVE: The purpose of this study was to establish longitudinal reference ranges for fetal ultrasound biometry measurements and growth parameters in twin pregnancies. METHOD: A total of 200 uncomplicated twin pregnancies before 21 weeks of gestation were recruited for this prospective, longitudinal study. Women who abandoned follow-up, pregnancies with unknown outcomes or pregnancies with complications were excluded. Ultrasound scans were performed every three weeks, and biparietal and occipitofrontal diameters, head and abdominal circumferences, and femur diaphysis length measurements were obtained for each fetus at each visit. Estimated fetal weight, biparietal/occipitofrontal diameter, head circumference/abdominal circumference, and femur diaphysis length/abdominal circumference ratios were also calculated. Multilevel regression analysis was performed on normalized data. RESULTS: A total of 807 ultrasound examinations were performed in 125 twin pregnancies between 14 and 38 weeks of gestation (6.5±1.4 scans/pregnancy). Regression analysis demonstrated significant correlations for all variables with gestational age, namely log of the biparietal diameter (r = 0.98), log of the occipitofrontal diameter (r = 0.98), log of the head circumference (r = 0.99), log of the abdominal circumference (r = 0.98), square root of the femur length (r = 0.99), log of the estimated fetal weight (r = 0.99), biparietal/occipitofrontal ratio (r = -0.11), head/abdomen circumference ratio (r = -0.56), and log of the femur length/abdominal circumference ratio (r = 0.61). Values corresponding to the 10th, 50th, and 90th percentiles for estimated fetal weight at 28, 32, and 36 weeks, respectively, were as follows: 937, 1,096, 1,284 g; 1,462, 1,720, 2,025 g; and 2,020, 2,399, 2,849 g. CONCLUSION: In twin pregnancies, fetal ultrasound biometry measurements and growth parameters show a significant correlation with gestational age.